Flora Diversity from Kersik Luway Nature Monument, East Kalimantan - SRI HARTINI (Society for Indonesian Biodiversity, 2007)
Kersik Luway is one area in Padang Luway Nature Reserve, East Kalimantan which have some potential plants. Ornamental plants are can be found in this area, which several of them are attractive and useful. The aims of the research were to inventory interesting flora diversity in Kersik Luway. The method used in this research were explorative method at the place. The result showed that there were approximately 18 species of interesting flora in Kersik Luway. The plants are Uaccinium varingiaefolium, Ficus deltoideus, Eugenia zeylanica, Rhodomyrtus tomentosu.s, Arthrophy°llarm diver.sifoliurrr, Nepenthes reimwurdticrna. Hown eoricrc°ea. C'oelngune pandurata, Coelogyne foerstermannii, Renanthera elongata, Grammatophyllum .speciosum, Cymbidium finlaysonianum, Stenochlaena palustris, Nephrolepis hirsutula, Davallia denticulata, Schizaea dichotoma, P.silotum nudum, and Lygodium microphyllum. The botanical information of eachspecies is presented in this paper.© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Flora, Kersik Luway, Nature Monument, East Kalimantan